El proceso penal hispano-musulmán: Competencia, iniciación y pruebas (Estudio realizado a traves de las fatuas contenidas en el Mi’yar de Al Wansharisi) - El-ouazzani Chahdi, Loubna (Cuadernos de Historia del Derecho, 2007)
This article is dedicated to the theoretical and practical study of the criminal process in Muslim Spain: this study has been made thanks to the information contained in the fatwas conserved in the famous Al Mi’yar book. The author of this article provides a description of the criminal process, the rules of the criminal procedure, the competent organs, as well as the particularitities of the andalusian criminal process. It all arises from the wealth of data contained in the fatwas compilations.